Peningkatan Kualitas dan Diversifikasi Produk Olahan Sukun - Purnomo Purnomo; Dwi Sulistyaningsih; R. Ery Wibowo Agung (Universitas Muhammadiyah Semarang, 2020)
The availability of breadfruit is abundant in the village of Meteseh in RW. X Tembalang District, Semarang City. BAROKAH farmers group develops breadfruit chip business. This group of farmers utilizes the abundantly available breadfruit fruit in the Meteseh area to make breadfruit chips. BAROKAH has problems in terms of limited equipment to support product manufacturing, and limited knowledge and skills in the processing and diversification of breadfruit preparations. The purpose of this activity is to develop a business through diversification of BAROKAH breadfruit processed products so that this business and all the people involved are able to become economically independent communities. It also improved product quality, creative and innovative skills, skills in using appropriate technology in the cutting, draining, and packaging of breadfruit processed products. The method used is to improve product quality, creative and innovative skills through the use of appropriate technology in the cutting, draining, and packaging of processed breadfruit products. In addition, diversification of breadfruit processed products was also developed. The results show that the application of appropriate technology has been able to increase the capacity of chopping, and the durability of processed products from breadfruit. In addition, the quality of processed breadfruit products has increased.